Development and externally validated prediction model of individualization of FSH starting dose in the depot GnRH agonist protocol for the early follicular phase - Fan, Wenqian; Ye, Tian; Du, Linqing; Tian, Lifeng; Kong, Huijuan (Frontiers in Endocrinology, 2025)
BackgroundEach controlled ovarian hyperstimulation(COH) protocol has its own unique mechanism and hormone pattern. The depot GnRHa protocol has a deeper down-regulation effect and favorable clinical pregnancy rates. The predictive model of the optimal follicle-stimulating hormone (FSH) starting dose in the early follicular phase depot GnRH agonist (EFDGa) protocol has not been reported. Our study was made to explore predictive indicators for determining the optimal FSH starting dose in patients undergoing ovarian stimulation with the EFDGa protocol in assisted reproductive technology (ART), and to develop and validate a nomogram prediction model for the starting dose of FSH.MethodsThis retrospective study included 2733 cycles who underwent fresh cycle transplantation at two large teaching hospitals in China from January to December 2022: center 1 (Reproductive Medicine Center of first affiliated Hospital of Zhengzhou University) provided the data for modelling (n = 938) and internal testing (n = 400), and center 2 (Reproductive Medicine Center of Jiangxi Maternal and Child Health Hospital) provided the data for external testing (n = 1109). Patient demographics, including age, anti-Mullerian hormone (AMH) levels, baseline endocrine profile, and body mass index (BMI), along with information on ovulation stimulation, were collected. Univariate and multivariate linear regression models were used to identify factors influencing the FSH starting dose. A nomogram for the ideal FSH starting dose was developed based on these factors and validated internally and externally. Bland and Altman plots and paired t-tests were conducted to verify the concordance between groups.ResultsMultivariate analysis revealed that patient age, BMI, basal FSH, AMH, and antral follicle count (AFC) were indicators of FSH starting dose. The regression model for predicting FSH starting dose was determined as: Initial FSH dose = 62.957 + 1.780*AGE(years) +4.927*BMI (kg/m²) +1.417*bFSH (IU/ml) - 1.996*AFC - 48.174*AMH (ng/ml). Bland and Altman analysis showed good agreement in the internal validation (bias: 0.583, SD of bias: 33.07IU, 95%LOA: -69.7 to 68.5IU b). Furthermore, validating the model on external cohort (center 2) confirmed that nomogram prediction model is an accurate predictor of FSH starting dose ((bias: -1.437, SD of bias: 38.28IU; 95%LOA: -80.0 to 77.1IU).ConclusionsWe established a model for effectively predicting the ideal FSH starting dose, with the nomogram model providing an intuitive representation of the data. The predictive model demonstrates practical utility, effectively initiating a proper ovarian response and preventing adverse ovarian reactions or the occurrence of ovarian hyperstimulation syndrome. As more IVF cycles are being generated in the future, this model will be valuable in clinicians using basic parameters to assess proper initial dose of FSH.